Educational Level of Childhood Brain Tumor Survivors: Results from a German Survey - Pfitzer, C.; Zynda, A.; Hohmann, C.; Keil, T.; Borgmann-Staudt, A. (Klinische Pädiatrie, 2013)
Among adult survivors of childhood brain tumors in Germany, we assessed their educational level and examined potentially influencing factors.A questionnaire was sent to 505 childhood brain tumor survivors listed in the German Childhood Cancer Registry. 203/505 (40.2%) patients with treatment and educational data were included in the analysis.Of the included brain tumor survivors 54.7% (111/203) were male, the median age was 11.0 (1–15) years at diagnosis and 22.0 (19–37) years at the time of the survey. 34.8% (95%-CI 25.1–44.5) of female and 34.9% (26.0–43.8) of male survivors achieved a high school diploma. Survivors who had received irradiation had less likely obtained a high school diploma compared to those without irradiation. However, this association was statistically not significant: for either craniospinal or tumor irradiation adjusted odds ratio was 0.54 (0.08–3.76); for those with a combination of craniospinal and tumor irradiation 0.51 (0.07–3.59). Participants aged 6–10 years at diagnosis achieved a higher educational level 2.24 (0.45–11.25) compared to younger patients.A third of the childhood brain tumor survivors who participated in our survey obtained the highest school leaving certificate. This may be biased by an overrepresentation of well-educated survivors without major cancer-related late effects. The influence of the patients’ strong motivation following a severe illness combined with the intensive psychosocial and/or pedagogical support on education needs to be examined in future studies.
Keywords: education; brain tumor; irradiation; posterior fossa tumors; children